Strategies to improve anxiety and depression in patients with COPD: a mental health perspective - Tselebis A (Dove Medical Press, 2016)
Athanasios Tselebis,1 Argyro Pachi,1 Ioannis Ilias,2 Epaminondas Kosmas,3 Dionisios Bratis,1 Georgios Moussas,1 Nikolaos Tzanakis4,5 1Psychiatric Department, “Sotiria” General Hospital of Chest Disease, Athens, Greece; 2Endocrinology Department, “Elena Venizelou” Hospital, Athens, Greece; 3Pulmonary Department, “Metropolitan” General Hospital, Athens, Greece; 4Department of Thoracic Medicine, 5Social Medicine, Laboratory of Epidemiology, University of Crete Medical School, Heraklion, Greece Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease characterized by progressive and only partially reversible symptoms. Worldwide, the incidence of COPD presents a disturbing continuous increase. Anxiety and depression are remarkably common in COPD patients, but the evidence about optimal approaches for managing psychological comorbidities in COPD remains unclear and largely speculative. Pharmacological treatment based on selective serotonin reuptake inhibitors has almost replaced tricyclic antidepressants. The main psychological intervention is cognitive behavioral therapy. Of particular interest are pulmonary rehabilitation programs, which can reduce anxiety and depressive symptoms in these patients. Although the literature on treating anxiety and depression in patients with COPD is limited, we believe that it points to the implementation of personalized strategies to address their psychopathological comorbidities. Keywords: COPD, anxiety, depression, pharmacological treatment, psychotherapy